Islamic architecture : its philosophy, spiritual significance & some early developments - Omer, Spahic (A.S. Noordeen, 2009)
Islamic architecture is not concerned about the form buildings only. Islamic architecture signifies a process where all the phases and aspects are equally imposratnt. It is almost impossible to identify a phase or an aspect in that process and consider it more important than the others. The Islamic architecture process starts with having a proper understanding and vision which leads to making a right intention. It continues with the planning, designing and building stages, and ends with attaining the net results and how people make use of and benefit from them. Islamic architecture is a fine blend of all these factors which are interwoven with the treads of the belief system, principles, teachings and values of Islam. This book discusses the philosophy and spiritual significance of Islamic architecture, as well as some early developments in relation to the evolution of its conspicuous identity. The character of the book's studies is a philosopical, or a conceptual, rather than an empirical one. The book is divided into four chapters: 1. Towards an understanding of Islamic architecture 2. A conceptual framework for Islamic architecture 3. Prophet Muhammad (pbuh) and Islamic architecture 4. Islamic architecture after Prophet Muhammad (pbuh)